165k views
5 votes
Hey:) can you please help me posted picture of question

Hey:) can you please help me posted picture of question-example-1

1 Answer

6 votes
Answer:
x² + 10x + 25

Step-by-step explanation:
Before we begin, remember the following:
(a + b)(a + b) = (a + b)² = a² + 2ab + b²

Now, for the given we have:
(x + 5)(x + 5)
We can note that the two brackets are identical.
Therefore, we can apply the above rule as follows:
(x + 5)(x + 5) = (x + 5)²
= (x)² + 2(x)(5) + (5)²
= x² + 10x + 25

Hope this helps :)
User Urso
by
5.8k points